2016
DOI: 10.1016/j.tjog.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum mental health in relation to sociocultural practices

Abstract: Cultural practices could not be perceived as protective mechanisms that protect women from PPD in this traditional society. However, health professionals should be familiar with postpartum beliefs and practices that could support mothers in the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…After exclusion of 67 records in full text review, 84 records were assessed for quality. Lastly, 58 articles on PND [ 39 95 ] and 17 [ 56 , 58 , 83 , 85 , 86 , 89 – 91 , 95 103 ] articles on adverse infant health outcomes were assessed as good quality and were included in quantitative analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion of 67 records in full text review, 84 records were assessed for quality. Lastly, 58 articles on PND [ 39 95 ] and 17 [ 56 , 58 , 83 , 85 , 86 , 89 – 91 , 95 103 ] articles on adverse infant health outcomes were assessed as good quality and were included in quantitative analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prevalensi depresi pascamelahirkan terus meningkat di seluruh dunia. Walaupun begitu, masih sedikit yang mencari pengobatan dan perawatan dari tenaga professional terutama di Negara berkembang dimana hampir dari 80% kasus tidak mencari pengobatan dan tidak di diagnosa oleh tenaga professional (1).…”
Section: Pendahuluanunclassified
“…Ia menyebutkan penggunaan perawatan dan kepercayaan tradisonal pada ibu maupun bayi dapat mengurangi risiko depresi pascamelahirkan (8). Penelitian yang dilakukan di Iran mengungkapkan hal sebaliknya, penelitian tersebut menyebutkan bahwa tidak terdapat hubungan antara kepercayaan dan perawatan tradisional pada masa nifas dengan depresi pascamelahirkan (1).…”
Section: Hasilunclassified
See 1 more Smart Citation
“…Such experience can be influenced by societal and cultural interpretation and labelling of symptoms. Previous quantitative and qualitative studies have shown that there was a link between sociocultural factors and PND (Abdollahi, Etemadinezhad & Lye, 2014;Gao et al, 2010). Within Asian culture, the traditional postnatal practice of staying inside the house for a month was described by the women as contributing to PND (Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%